Regional Heterogenity and Conditional Convergence - Michael Beenstock; Daniel Felsenstein (European Regional Science Association (ERSA), 2005)
This paper stresses the importance of accounting for regional heterogenity in the dynamic analysis of regional economic disparities. Studies of regional growth invariably presume regions are homogenous in that their socio-demographic composition is assumed to be broadly similar. We argue that any analysis of regional convergence needs to be tested conditionally, i.e. conditional upon the socio-demographic structure of the workers in the various regions. To this end, we estimate various measures of conditional regional earnings inequality using Israeli regional data for the period 1991-2002. Our results show that much of the regional earnings inequality may be accounted for by the conditioning variables. Both in measures of regional convergence and regional mobility, conditioning makes a large difference to the results accounting for up to half of the observed levels of inequality. Ignoring regional heterogeneity may therefore lead to serious over-estimation of the underlying level of regional inequality.
Keywords: 330